Samurai Wasp Trissolcus japonicus (Ashmead) (Insecta: Hymenoptera: Scelionidae: Telenominae) - Anita S. Neal (EDIS, 2017)
Includes: Introduction - Distribution - Description and Life Cycle - Hosts - Selected References